2017
DOI: 10.1021/acsami.7b11561
|View full text |Cite
|
Sign up to set email alerts
|

Monomer: Design of ZnO Nanostructures (Nanobush and Nanowire) and Their Room-Temperature Ethanol Vapor Sensing Signatures

Abstract: Ethanol serves as a biomarker as well as a chemical reagent for several applications and has been predominantly used as an alternative fuel (E10 and E85). Development of sensors for the detection and monitoring of ethanol vapor at lower operating temperatures has gathered momentum in the recent past. In this work, we reported the synthesis of self-assembled ZnO nanowires using electrospun technique without using any external surfactants or capping agents and their room temperature ethanol sensing properties. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(17 citation statements)
references
References 68 publications
0
17
0
Order By: Relevance
“…The activation energy of the deposited sensing elements was calculated using the Arrhenius equation (eqn (11)), 42,43…”
Section: View Article Onlinementioning
confidence: 99%
See 1 more Smart Citation
“…The activation energy of the deposited sensing elements was calculated using the Arrhenius equation (eqn (11)), 42,43…”
Section: View Article Onlinementioning
confidence: 99%
“…As far as the properties of gas sensing elements are concerned, the morphology, defect state, crystallinity, and surface roughness decide the selective detection of target analytes. 21,42 Enhanced crystallinity with crystal reorientation, shi in the defect states, elongated growth of aggregated nanograins with improved roughness prole of the lm deposited at 773 K, could have enhanced the surface with more reactive oxygen sites in-turn resulted in the increased sensing response. On the Fig.…”
Section: View Article Onlinementioning
confidence: 99%
“…In gas sensors, the pore properties are important factors because they allow adsorbates into internal surfaces to ensure adequate adsorption performance. For example, highly sensitive and selective gas sensors of ZnO nanowires/NPs were able to detect ethanol and acetone quickly and accurately [187,188]. Nano-brush and pearl chain-like ZnO nanowires were developed for the selective and sensitive detection of ethanol [187].…”
Section: Biomedical Applicationsmentioning
confidence: 99%
“…For example, highly sensitive and selective gas sensors of ZnO nanowires/NPs were able to detect ethanol and acetone quickly and accurately [187,188]. Nano-brush and pearl chain-like ZnO nanowires were developed for the selective and sensitive detection of ethanol [187]. Zhou et al [188] reported an interlocking p + n field-effect transistor circuit of Mn-doped ZnO NPs for detecting acetone as low as 2 ppm, even under conditions of high relative humidity (>85%).…”
Section: Biomedical Applicationsmentioning
confidence: 99%
“…The resistive ethanol sensors used semiconducting metal oxides (MOS) as sensing materials are popular due to their advantages, such as cheap, nontoxic, stable, simple processing, and higher sensitivity performance [6][7][8]. Typically, various nanostructured MOS including nanowires, nanoplates, hollow spheres, and heterostructures can greatly enhance the diffusion of analyte gases and facilitate the charge transport, leading to high sensitivity and fast sensing-recovery process [9][10][11][12][13][14][15][16][17][18]. However, most of the reported sensors are fabricated by drop-coating or screen printing the nanostructured MOS solution onto ceramic tubes or plates, which results in large sensor-to-sensor variations, large size, and high power consumption of 200-1000 mW [7,[19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%